The role of supervisors for change acceptance - Neves, Pedro (Henry Stewart Talks, 2010)
Scientific approaches to change, Importance of a micro-level approach to change, Employees' reactions to change, Consequences of employees' reactions to change for organizations, Supervisory tasks, Supervisor responsibilities' during change, The importance of supervisors, Case study